TINJAUAN HUKUM ISLAM TERHADAP HUTANG PIUTANG DENGAN JAMINAN SAWAH - Anggara, Falufi; Safitri, Nuri (EKSYDA: Jurnal Studi Ekonomi Syariah, 2022)
Debt and credit transactions are permissible in Islam as long as they do not contradict Islamic principles. In practice, such transactions are often supported by collateral to strengthen the agreement between the involved parties. This study aims to examine the practice of debt agreements with paddy field collateral in Gunung Tiga Village, Batanghari Nuban Subdistrict, East Lampung, and to analyze the Islamic legal perspective on the prohibition of taking collateral before the contract period ends. The research employs a qualitative descriptive approach, with data collected through interviews and documentation. The findings indicate that the debt practices in the village comply with the pillars and conditions of a valid contract in Islamic law. Taking the collateral before the end of the contract is not permitted unless the debtor is unable to repay the debt. In such cases, the collateral serves as a substitute for the unpaid debt, functioning as a form of protection for the creditor's rights. This research is expected to contribute theoretically to the body of knowledge in Islamic jurisprudence and practically as a reference for the implementation of debt agreements with collateral.